At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the product function [tex]\((m \cdot n)(x)\)[/tex], where [tex]\(m(x) = x^2 + 4x\)[/tex] and [tex]\(n(x) = x\)[/tex], we need to calculate:
[tex]\[ (m \cdot n)(x) = m(x) \cdot n(x) \][/tex]
First, let's define the two given functions:
1. [tex]\( m(x) = x^2 + 4x \)[/tex]
2. [tex]\( n(x) = x \)[/tex]
Now, we compute the product function by multiplying these functions together:
[tex]\[ (m \cdot n)(x) = m(x) \cdot n(x) \][/tex]
Substitute [tex]\( m(x) \)[/tex] and [tex]\( n(x) \)[/tex] into the equation:
[tex]\[ (m \cdot n)(x) = (x^2 + 4x) \cdot x \][/tex]
Next, we distribute [tex]\( x \)[/tex] in the expression [tex]\( (x^2 + 4x) \cdot x \)[/tex]:
[tex]\[ (m \cdot n)(x) = x^2 \cdot x + 4x \cdot x \][/tex]
Now, calculate each term:
[tex]\[ x^2 \cdot x = x^3 \][/tex]
[tex]\[ 4x \cdot x = 4x^2 \][/tex]
Combine the results:
[tex]\[ (m \cdot n)(x) = x^3 + 4x^2 \][/tex]
So, the product function [tex]\((m \cdot n)(x)\)[/tex] is:
[tex]\[ (m \cdot n)(x) = x^3 + 4x^2 \][/tex]
Thus, we have successfully found the product of the functions [tex]\(m(x)\)[/tex] and [tex]\(n(x)\)[/tex]:
[tex]\[ (m \cdot n)(x) = x^3 + 4x^2 \][/tex]
[tex]\[ (m \cdot n)(x) = m(x) \cdot n(x) \][/tex]
First, let's define the two given functions:
1. [tex]\( m(x) = x^2 + 4x \)[/tex]
2. [tex]\( n(x) = x \)[/tex]
Now, we compute the product function by multiplying these functions together:
[tex]\[ (m \cdot n)(x) = m(x) \cdot n(x) \][/tex]
Substitute [tex]\( m(x) \)[/tex] and [tex]\( n(x) \)[/tex] into the equation:
[tex]\[ (m \cdot n)(x) = (x^2 + 4x) \cdot x \][/tex]
Next, we distribute [tex]\( x \)[/tex] in the expression [tex]\( (x^2 + 4x) \cdot x \)[/tex]:
[tex]\[ (m \cdot n)(x) = x^2 \cdot x + 4x \cdot x \][/tex]
Now, calculate each term:
[tex]\[ x^2 \cdot x = x^3 \][/tex]
[tex]\[ 4x \cdot x = 4x^2 \][/tex]
Combine the results:
[tex]\[ (m \cdot n)(x) = x^3 + 4x^2 \][/tex]
So, the product function [tex]\((m \cdot n)(x)\)[/tex] is:
[tex]\[ (m \cdot n)(x) = x^3 + 4x^2 \][/tex]
Thus, we have successfully found the product of the functions [tex]\(m(x)\)[/tex] and [tex]\(n(x)\)[/tex]:
[tex]\[ (m \cdot n)(x) = x^3 + 4x^2 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.